ENHANCING MILK YIELD AND QUALITY IN DAIRY COWS THROUGH INCLUSION OF ORANGE-FLESHED FODDER PUMPKIN IN THE DIET (Neo Science Peer Reviewed Journal, 2025)
This study examines the effects of incorporating orange-fleshed fodder pumpkin into the diet of dairy cows on milk yield, milk composition, and feed efficiency. The research revealed that the pumpkin variety used, due to its high digestibility, rich energy content, and beta-carotene levels, improved overall cow health and lactation performance. Experimental results indicated an increase in milk fat, dry matter, and energy content of milk, as well as better feed conversion efficiency. Economic analysis demonstrated that using this locally available and inexpensive feed source is cost-effective and enhances farm profitability. These findings support the inclusion of orange-fleshed fodder pumpkin as a practical nutritional supplement in dairy cow diets.